Implementation of the Problem Based Learning Model to Improve Understanding of Dhuha, Tahajud, and Friday Prayer Material in Elementary School Students - Wiyantiningsih; Siti Nur Jannah (FITK UIN Walisongo Semarang, 2025)
This research is motivated by the low learning outcomes of students in the subject of Islamic Religious Education (PAI), especially in the mastery of dhuha, tahajud, and Friday prayer materials in grade IV of SD Negeri 1 Tunahan. The purpose of the study is to analyze the improvement of student learning outcomes through the application of the Problem Based Learning (PBL) model and describe the implementation of the model along with its supporting and inhibiting factors. The research uses a Classroom Action Research (PTK) approach with a two-cycle design that includes the stages of planning, implementation, observation, and reflection. The research subjects consist of 15 grade IV students in the 2024/2025 school year. Data was collected through learning outcome tests, observations, interviews, questionnaires, and documentation, then analyzed descriptively, qualitatively, and quantitatively. The results showed a significant improvement: learning completeness increased from 33% in the pre-cycle to 87% in the second cycle, accompanied by an increase in the activity of teachers (average 4.9) and students (average 3.8) who were categorized as satisfactory and good, respectively. The PBL model has been proven to be effective in creating active, interactive, and contextual learning, thereby strengthening students' understanding of PAI materials. These findings make an original contribution to the application of a problem-based approach to religious learning in primary schools, while offering an alternative to relevant and applicable learning strategies.